Formula Optimization and Sensory Analysis of Functional Collagen Drink from Butterfly Pea Flower (Clitoria ternatea L.) and Red Guava (Psidium guajava L.) - Anjar Asmarani Widya Nabilah; Ela Marcelia; Tri Dewanti Widyaningsih; Kiki Fibrianto (Biology, Medicine, & Natural Product Chemistry, 2025)
The global market for functional beverages is experiencing rapid growth as consumer awareness for healthy lifestyles increases. The objective of this study is to ascertain the physical characteristics, optimal formula, and organoleptic quality of functional collagen beverages derived from a blend of bayang flower (Clitoria ternatea L.), red guava (Psidium guajava L.), and emprit ginger. In this study, an extreme vertex design was employed in conjunction with Minitab 19 to extract the materials. The extraction process was carried out using the following methods: telang flowers were subjected to a drying process at 40°C for 24 hours, followed by extraction with water at 60°C for 30 minutes; ginger emprit was dried at 60°C for 24 hours and then extracted at 55°C for 15 minutes; and red guava was blended with water at a 1:1 ratio. The total phenolic content was analyzed using the Folin-Ciocalteu method, while antioxidant activity was evaluated through the use of the DPPH method. Finally, sensory evaluation was conducted employing a hedonic test, which was completed by 100 untrained panelists. The optimal formula obtained was 50% telang flower extract, 30% red guava juice, 15% ginger emprit extract, and 5% collagen hydrolysate (desirability value 0.8288), resulting in antioxidant activity of 316.45 mg TE/100 ml and total phenolic content of 247.33 mg GAE/L. The sensory evaluation revealed that the subject demonstrated moderate acceptance, as indicated by an average preference score of 3.51. The combination of bay flower extract and guava juice exhibited a synergistic effect in enhancing antioxidant activity, while guava juice contributed significantly to the total phenolic content. Notwithstanding the favorable reception, the robust ginger flavor, elevated viscosity, diminished clarity, and textural characteristics.